Generation of Recombinant Vaccinia Viruses. (13th February 2018) - Wyatt, Linda S.; Earl, Patricia L.; Moss, Bernard
Abstract: This unit describes how to infect cells with vaccinia virus and then transfect them with a plasmid‐transfer vector or PCR fragment to generate a recombinant virus. Selection and screening methods used to isolate recombinant viruses and a method for the amplification of recombinant viruses are described. Finally, a method for live immunostaining that has been used primarily for detection of recombinant modified vaccinia virus Ankara (MVA) is presented. © 2017 by John Wiley & Sons, Inc.